"Everybody Needs to Do Their Part, So We Can Get This Under Control." Reactions to the Norwegian Government Meta‐Narratives on COVID‐19 Measures. Issue 5 (17th February 2021) - Moss, Sigrun Marie; Sandbakken, Ella Marie
Abstract : On March 12, 2020, the Norwegian government put the country on lock‐down to get the COVID‐19 situation under control. Making people adhere to restrictive measures is difficult. Even so, the Norwegian government largely succeeded in getting the population to comply and became the first European country to announce control over the situation. In this study, we ask what narratives the government put forth in their communication of the measures and how these measures were handled and made sense of in personal narratives at the general population level. We base our discussion on near daily government press conferences in March–April, as well as qualitative interviews with 16 individuals. Using a cultural narrative perspective on the data, we tie these meta‐narratives and personal narratives together. Persuading people to comply with prevention and control measures in a crisis is crucial, and our study shows the importance of the selection of meta‐narratives. There will be cultural differences in governance and receptiveness of the population across different settings, and our study suggests that governments will have to balance where on different continua they place their COVID‐19 narratives, balancing freedom up against restrictions, hope against fear, and individualism against solidarity. Highlights Practitioners and policymakers need to be aware of the narratives they use to communicate COVID‐19 measures and how these fit with the overarching narratives in society. Using narratives that resonate as much as possible with people's personal narratives may aid meaning making and compliance. Practitioners also need to balance where on different continua they place their COVID‐19 narratives: balancing freedom against restrictions, hope against fear, and individualism against solidarity. The ideal placement of the narratives depends on culture and context. Ambiguously communicated messages make room for subjective interpretations in people's everyday lives, allowing for differing and conflicting personal narratives. Therefore, communication should be as concrete and consistent as possible.